The dynamic interplay of inequality and trust: an experimental study - Ben Greiner; Axel Ockenfels; Peter Werner (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the interplay of inequality and trust in a dynamic game, in which trust increases efficiency and thus allows higher growth of the experimental economy in the future. We find that trust is initially high in a treatment starting with equal endowments, but decreases over time. In a treatment with unequal endowments, trust is initially lower yet remains relatively stable. The difference seems partly due to the fact that equal starting positions increase subjects' inclination to condition their trust decisions on wealth comparisons, whereas conditional trust is much less prevalent with unequal initial endowments. As a result, with respect to efficiency, the initially more unequal economy fares worse in the short run but better in the long run, and the disparity of wealth distributions across economies mitigates over time.
Keywords: C73; C92; D63; E25; O15; 330; inequality; trust; growth; laboratory experiments; Soziale Ungleichheit; Vertrauen; Dynamisches Spiel; Test; Theorie; Schätzung